Pengaruh Intellectual Capital, Kepemimpinan, Budaya Organisasi, dan Keberlanjutan Lingkungan terhadap Kinerja Perusahaan dengan Inovasi sebagai Pemoderasi - Nurhidayati, Febriana; Subroto, Waspodo Tjipto; Listiadi, Agung (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
This study analyze the impact of intellectual capital, leadership, organizational culture, and environmental sustainability on company performance, moderated by product innovation. The study employs descriptive quantitative research design using an explanatory research approach with SEM-PLS analysis. The sample consists of 86 employees holding managerial positions in Pegadaian Area Surabaya 1, selected using a purposive sampling. Hypothesis testing was conducted through a variance-based SEM approach with the Partial Least Square. The findings indicate that the intellectual capital does not significant affect company performance, whereas organizational culture, leadership, and environmental sustainability have a significant impact. The moderation of intellectual capital, leadership, organizational culture, and environmental sustainability by product innovation does not influence company performance. This suggests that product innovation does not strengthen the impact of these variables on company performance.